Idiopathic perforation of acalculous gallbladder after insertion of a transpapillary pancreatic stent - Katagiri, Tomoko; Irisawa, Atsushi; Wakabayashi, Hiroto; Tsunoda, Takuya; Tomoda, Hiroyuki; Saito, Ryo; Kinuta, Shunji (Endoscopy International Open, 2016)
Background and study aims: Endoscopic retrograde pancreatocholangiography (ERCP) is associated with many types of adverse events (AEs) but idiopathic perforation of the gallbladder (IPGB) is very rare. Pancreatobiliary reflux is one of the factors involved with occurrence of IPGB 1. Here we present a case of acalculous gallbladder perforation as an AE following the insertion of an indwelling endoscopic nasal pancreatic drainage (ENPD) tube (a pancreatic stent) to obtain pancreatic fluid. In this case, acute pancreatobiliary reflux might have been caused by the insertion of the ENPD-tube.